2015
DOI: 10.1111/jvp.12257
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of enrofloxacin in Nile tilapia (Oreochromis niloticus) after a single oral administration in medicated feed

Abstract: The objective of this study was to evaluate the disposition kinetics of enrofloxacin (ENR) in the plasma and its distribution in the muscle tissue of Nile tilapia (Oreochromis niloticus) after a single oral dose of 10 mg/kg body weight via medicated feed. The fish were kept at a temperature between 28 and 30 °C. The collection period was between 30 min and 120 h after administration of the drug. The samples were analyzed by high-performance liquid chromatography with a fluorescence detector (HPLC-FLD). The ENR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…For antibiotics commonly used in aquaculture, ENRO, FFC, OTC and TAP, the isolates were classified as susceptible (MIC ≤ 0.096 µg/ml, ≤4 µg/ml, ≤1 µg/ml and ≤ 8 µg/ml, respectively), intermediately susceptible (0.096 < MIC ≤1.92, ≤ 4 µg/ml, 8 µg/ml and 2 µg/ml, respectively) or resistant (MIC > 1.92 µg/ml, >8 µg/ml, >2 µg/ml and >8 µg/ml, respectively) following the alternative interpretative criteria suggested by CLSI (2014) (Agustín et al., 2019; Assane et al., 2019; Teles et al., 2015). MBC‐to‐MIC ratio was used to identify antimicrobial agents as either bactericidal or bacteriostatic.…”
Section: Methodsmentioning
confidence: 99%
“…For antibiotics commonly used in aquaculture, ENRO, FFC, OTC and TAP, the isolates were classified as susceptible (MIC ≤ 0.096 µg/ml, ≤4 µg/ml, ≤1 µg/ml and ≤ 8 µg/ml, respectively), intermediately susceptible (0.096 < MIC ≤1.92, ≤ 4 µg/ml, 8 µg/ml and 2 µg/ml, respectively) or resistant (MIC > 1.92 µg/ml, >8 µg/ml, >2 µg/ml and >8 µg/ml, respectively) following the alternative interpretative criteria suggested by CLSI (2014) (Agustín et al., 2019; Assane et al., 2019; Teles et al., 2015). MBC‐to‐MIC ratio was used to identify antimicrobial agents as either bactericidal or bacteriostatic.…”
Section: Methodsmentioning
confidence: 99%
“…These drugs act by preventing DNA supercoiling through the inhibition of bacterial DNA gyrase (Dimitrova, Haritova, Dinev, Moutafchieva, & Lashev, ). The pharmacokinetics of several fluoroquinolones have previously been reported in fish species, including difloxacin in gibel carp (Cao, Zhang, He, Zheng, & Yang, ), sarafloxacin in crucian carp (Fang, Zhou, & Liu, 2016b), and enrofloxacin in grass carp (Xu, Wang, Yang, & Lu, ), Nile tilapia (Teles, Branco, Del Bianchi, Pilarski, & Reyes, ), snakehead fish (Fang et al., ), and crucian carp (Fan et al., ).…”
Section: Introductionmentioning
confidence: 96%
“…Enrofloxacin serves as a last-line treatment in aquaculture, and it effectively treats the bacterial infections caused by F. columnare (6), A. hydrophila (9), and A. sobria (10). The plasma pharmacokinetics of enrofloxacin has been reported in some fish species, such as crucian carp (11,12), large yellow croaker (13), tilapia (14), snakehead fish (15), brown turbot (16), and salmonids (17). In addition to those pharmacokinetics studies, the tissue distribution of enrofloxacin has also been reported in aquaculture species, including northern snakeheads (18), rainbow trout (19,20), grass carp (21), largemouth bass (22), and pacu (23).…”
Section: Introductionmentioning
confidence: 99%